Influence of corporate philanthropy on economic performance - Navickas, Valentinas; Kontautienė, Rima (Business: Theory and Practice, 2011)
The authors examine the impact of corporate philanthropic activities on their economic performance. Corporate philanthropy is defined as a component of corporate social responsibility which opens new opportunities for business relationship with stakeholders and is contributing to promotion of corporate social involvement and to diffusion of the social responsibility principles implementation. With an emphasis on the positive impact of philanthropic activities on corporate economic performance, the benefits of corporate philanthropic activities to future revenue growth, characterized by improvement in corporate image, reputation development, business growth and customer loyalty are considered, as well as other economic benefits such as improved recruitment, the growth of innovation, value of share growth, sales growth, the increase in employee morale and productivity, the rise of customer curiosity to know companies which carry out philanthropic actions. This paper reviews the corporate philanthropic activities in Lithuania in recent years and focuses on the relationship between philanthropic activities of corporation “TEO LT” and its financial performance improvements. Having examined the issue of the impact of corporate philanthropic activities on its economic performance, the authors found that corporate philanthropic activities have a positive impact not only on corporate financial indicators related to future revenue growth, but also on other economic indicators, as well as on the relationship with all stakeholders. Įmonių filantropijos poveikis jų ekonominės veiklos rezultatams Santrauka Straipsnyje nagrinėjama filantropinės įmonių veiklos įtaka jų ekonominiams rezultatams. Įmonių filantropija apibūdinama kaip įmonių socialinės atsakomybės komponentė, atverianti joms naujų galimybių santykiuose su suinteresuotomis šalimis, prisidedanti prie socialinio aktyvumo skatinimo bei socialinės atsakomybės principų įgyvendinimo sklaidos. Akcentuojant teigiamą filantropinės veiklos įtaką įmonių ekonominiams rezultatams nagrinėjama įmonių filantropinės veiklos teikiama nauda būsimųjų pajamų augimui, pasireiškianti įmonių įvaizdžio sustiprėjimu, reputacijos augimu, klientų lojalumo įmonėms augimu bei kita ekonomine nauda: darbuotojų samdos pagerėjimas, teigiami jų moralės pokyčiai, inovacijų didėjimas, akcijų vertės augimas, pardavimo masto augimas, produktyvumo didėjimas, klientų smalsumo pažinti įmones, vykdančias filantropines akcijas, augimas. Straipsnyje apžvelgiama Lietuvos įmonių filantropinė veikla pastaraisiais metais bei tiriamas sąryšis tarp aktyvėjančios AB „TEO LT“ filantropinės veiklos ir jos finansinių rezultatų gerėjimo. Ištyrę įmonių filantropijos poveikį jų ekonominiams rodikliams straipsnio autoriai nustatė, kad filantropinė veikla teigiamai veikia ne tik jų finansinius rezultatus, susijusius su būsimų pajamų augimu, bet ir kitus ekonominius rodiklius. Reikšminiai žodžiai: įmonių socialinė atsakomybė, filantropija, filantropija Lietuvoje, filantropijos poveikis verslui, konkurencingumas.